Micha - Zapff, Burkard M. (W. Kohlhammer GmbH, 2020)
Significant parts of the text of Micah were probably written as part of a book of several prophets & or twelve prophets & and can therefore only be adequately understood and interpreted in that context. A piece of Old Testament theological history thus becomes visible here that was not primarily concerned with the message of a single, individual prophetic figure, but above all with general testimony to YHWH=s speech and action in the history of his people. Zapff demonstrates this by reflecting diachronically on the results of a synchronic interpretation in order to trace the process of the creation of the text of Micah and its theological message. Wesentliche Teile der Michaschrift sind wahrscheinlich im Kontext eines Mehr- oder Zwölfprophetenbuches entstanden und können deshalb nur in diesem Zusammenhang angemessen verstanden und interpretiert werden. So wird hier ein Stück alttestamentlicher Theologiegeschichte sichtbar, der es nicht in erster Linie um die Aussage der einzelnen, individuellen Prophetengestalt ging, sondern vor allem um das allgemeine Zeugnis vom Sprechen und Handeln JHWHs in der Geschichte seines Volkes. Dies zeigt Zapff, indem er die Ergebnisse seiner synchronen Auslegung diachron reflektiert, um den Entstehungsprozess der Michaschrift und ihrer theologischen Aussage nachzuzeichnen
Keywords: Altes Testament; Dodekapropheton; Exegese; Jesaja; Kommentar; Prophetie